Investigating the role of UTAUT and e-service quality in internet banking adoption setting. Issue 3 (24th April 2019) - Rahi, Samar; Abd.Ghani, Mazuri
Abstract : Purpose: Technology adoption is a great challenge in the banking sector of Pakistan. A recent report issued by state bank of Pakistan revealed that there is a squeak growth, only 3 percent, in internet banking adoption. In order to effectively delve into the issue of internet banking adoption, the purpose of this paper is to use unified theory of acceptance and use of technology factors, namely performance expectancy and effort expectancy and e-service quality (E-SQ), as theoretical lens for this study. Design/methodology/approach: The research model was empirically tested using 398 valid responses from customers of commercial banks in Pakistan. The theoretical model was tested using structural equation modeling. Findings: Findings indicate that performance expectancy, effort expectancy, website design, customer service, assurance and reliability have direct influence on user intention to adopt internet banking. Results revealed that approximately 79 percent of variance in user intention to adopt internet banking was explained by predictors. In addition, the mediating role of performance expectancy and effort expectancy among website design, customer service and user intention was also confirmed. Practical implications: For researchers, this study provides a base of integrated technology model and it suggests using this model in other online domains such as mobile payment and online web-shopping for further refinement. For policymakers, understanding the key constructs is important to design, refine and implement new internet banking website that, in turn, will boost internet banking adoption trend among users of commercial banks. Originality/value: This paper makes a unique contribution toward information system and services marketing literature. The study schematized that website design, customer service, assurance and reliability are the key dimensions of E-SQ and significantly influence the user intention to adopt internet banking.